A Catechol‐Type Resveratrol Analog Manifests Antiangiogenic Action by Constructing an Efficient Catalytic Redox Cycle with Intracellular Copper Ions and NQO1. Issue 15 (13th July 2018) - Wang, Yi‐Hua; Dai, Fang; Zhou, Bo
Abstract : Scope: As part of our research project to understand why dietary polyphenols with the catechol skeleton tend to exhibit cancer chemopreventive activity, a catechol‐type resveratrol analog (3, 4‐dihydroxy‐ trans ‐stilbene [3, 4‐DHS]) was selected to probe its antiangiogenic effects and mechanisms. Methods and results: The antiangiogenic effects of 3, 4‐DHS on angiogenesis‐related endothelial cell functions were examined, including migration, invasion, and tube formation, and in vivo angiogenesis on a chick chorioallantoic membrane assay. The potential molecular mechanisms for the suppression of cell migration by 3, 4‐DHS were analyzed using various specific inhibitors. 3, 4‐DHS was identified as a potent angiogenesis inhibitor by constructing an efficient catalytic redox cycle with intracellular copper ions and NAD(P)H quinone oxidoreductase I to generate reactive oxygen species and thereby downregulate matrix metalloproteinase‐9. Conclusion: This work provides further evidence that dietary catechols manifest antiangiogenic activity by virtue of their copper‐dependent prooxidative instead of antioxidative role, and useful information for designing polyphenol‐inspired angiogenesis inhibitors. Abstract : A catechol‐type resveratrol analog (3, 4‐dihydroxy‐ trans ‐stilbene) is selected as a model of dietary catechol‐type molecules to probe its antiangiogenic effects and mechanisms. This molecule is capable of constructing an efficient catalytic redox cycle with intracellular copper ions and NQO1 to generate ROS (O2 − and H2 O2 ), thereby downregulating MMP‐9 and manifesting antiangiogenic action.